Oral implications by COVID-19. Topic review - Gutiérrez Flores, Rodolfo (2020)
Clinical manifestations that contributed to understanding the behavior of SARS-CoV-2 have been reported; the dermatological medical area has presented studies on the expression of COVID-19 in skin, for example, but in oral level there is limited information. The aim of this updated review of the literature is to analyze the implications of COVID-19 in the oral cavity through a retrospective cross-sectional study carried out through an electronic scan for the selection of detailed scientific information in PubMed through the NCBI, Virtual Health Library, and the Scielo, Redalyc, Dialnet, Latindex, Cochrane Library and LILACS databases, based on literature reviews, clinical case reports and letters to the editor related to SARS-CoV-2 / COVID-19 and its expression in oral mucosa, in the English and Spanish languages, of the present year 2020. The tissues of the oral cavity represent an initial structure susceptible to viral infection and oral fluids as transmission vehicles.